Gamification as an innovative strategy to increase motivation in teaching English to young learners in Uzbekistan - Dilnura Sharofova; Mukhabat Ikromovna Tursunova (Science and Education, 2026)
Motivation is one of the most important factors in successful foreign language learning. In recent years, gamification has become an innovative strategy in education. Gamification involves the use of game elements such as points, rewards, and competitions in the learning process. This article examines the role of gamification in increasing motivation among young learners in Uzbekistan. The study analyzes theoretical and practical aspects of gamification and its effectiveness in English language teaching. The findings show that gamification increases students’ interest, participation, and confidence. It creates a positive learning environment and reduces students’ anxiety. The article also presents innovative ideas for using gamification in Uzbek classrooms. The results suggest that gamification can improve the quality of English language education and support modern educational reforms.